2009
DOI: 10.1029/2009ja014213
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of ELF currents and electromagnetic fields into the Earth's equatorial ionosphere

Abstract: The penetration of extremely low frequency (ELF) transient electromagnetic fields and associated currents in the Earth's equatorial E-region plasma is studied theoretically and numerically. In the low-frequency regime, the plasma dynamics of the E-region is characterized by helicon waves since the ions are viscously coupled to neutrals while the electrons remain mobile. For typical equatorial E-region parameters, the plasma is magnetically insulated from penetration of very long timescale magnetic fields by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The resulting Cowling conductivity σC=σH2/σP2+1σP , is a few orders of magnitude larger than the Pedersen conductivity in the E region. For the case when magnetic fields are injected into the ionosphere by a ground‐based antenna from below [ Eliasson and Papadopoulos , 2009], it was found that the Cowling effect can lead to intense horizontal currents and vertical electric fields in the E‐region. For the case considered here, we see inFigure 8h that a sharp drop of the amplitude of B x at z ≈ 100 km is associated with the intense current component j y via Ampère's law Bx/z=μ0jy , and a large vertical electric field E z in Figure 8g.…”
Section: Dynamics Of Elf Waves Generated In the F2 Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting Cowling conductivity σC=σH2/σP2+1σP , is a few orders of magnitude larger than the Pedersen conductivity in the E region. For the case when magnetic fields are injected into the ionosphere by a ground‐based antenna from below [ Eliasson and Papadopoulos , 2009], it was found that the Cowling effect can lead to intense horizontal currents and vertical electric fields in the E‐region. For the case considered here, we see inFigure 8h that a sharp drop of the amplitude of B x at z ≈ 100 km is associated with the intense current component j y via Ampère's law Bx/z=μ0jy , and a large vertical electric field E z in Figure 8g.…”
Section: Dynamics Of Elf Waves Generated In the F2 Regionmentioning
confidence: 99%
“…Low‐frequency waves in the ionosphere, can be excited by lightning discharges [ Greifinger and Greifinger , 1976; Uman , 1987; Berthelier et al , 2008; Milikh et al , 1995], seismic events [ Hayakawa et al , 2006], and ionospheric heating by powerful high‐frequency (HF) transmitters [ Rietveld et al , 1984, 1987, 1989; Barr , 1998; Papadopoulos et al , 1990, 2005]. The injection of ELF electromagnetic waves into the equatorial E‐region by ground‐based antennas was suggested by Eliasson and Papadopoulos [2009], who found that induced strong horizontal currents and related vertical electric fields can be formed in a few kilometers thick layer, close to the plasma‐free space boundary. This effect is reminiscent of the equatorial electrojet [ Forbes and Lindzen , 1976; Forbes , 1981; Rishbeth , 1997; Rastogi , 1989] where a potential drop due to tidal motion along the equatorial line gives rise to an intense electron current by the Cowling effect.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the previous work [15], we assume a very simple model for the antenna, that of an equivalent infinite length wire in the y direction located at x = z = 0, so that,…”
Section: Interaction Model and Simulation Setupmentioning
confidence: 99%
“…However, the interaction of ELF range electromagnetic fields with E-region is relatively less understood. Eliasson and Papadopoulos [15] studied generation and penetration of the ELF current and electromagnetic fields into the equatorial E-region. They found that the interaction of the ELF pulsed and continuous wave fields with the equatorial E-region leads to the generation of both vertical and horizontal currents which penetrate into ionospheric layers as Helicon waves.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the electromagnetic perturbation in the neutral atmosphere is estimated by analytic expression, and the inversely spatial Fourier transform is applied to obtain the real space wave field (Eliasson and Papadopoulos, 2009;Eliasson et al, 2012).…”
Section: Xu Et Al: Numerical Study Of the Generation And Propagatmentioning
confidence: 99%